2007
DOI: 10.1590/s1678-77572007000500006
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride release of six restorative materials in water and pH-cycling solutions

Abstract: The fluoride release of restorative materials in deionized water has been the subject of many studies, but the behavior of these materials under conditions of acid challenge that simulates the oral cavity, needs to be further explored. Therefore, the aim of this study was to evaluate the fluoride release of restorative materials in two storage protocols: deionized water and pH- cycling system (demineralizing solution-pH 4.3 and remineralizing solution-pH 7.0) for 15 days. Eight disks of each material (Vitremer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 16 publications
1
30
0
2
Order By: Relevance
“…In fact, the most important finding is not the amount of Freleased from the material, but the Frelease pattern overtime. Accordingly, Garcez et al (13) found that the Frelease pattern from restorative materials were similar in deionized water and in solutions simulating pH-cycling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the most important finding is not the amount of Freleased from the material, but the Frelease pattern overtime. Accordingly, Garcez et al (13) found that the Frelease pattern from restorative materials were similar in deionized water and in solutions simulating pH-cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Since the restorative materials do not have similar composition, the discussion of the results are mainly based on the comparison of the cumulative Frelease pattern rather than the Frelease differences among materials at each day. The daily Frelease mean might be influenced by several factors, such as the storage medium, being of less importance to the scientific knowledge (13).…”
Section: Discussionmentioning
confidence: 99%
“…Although they may contain fluoride in the form of the radiopaque filler ytterbium trifluoride (YbF 3 ), its release seems insufficient for remineralization. 4 Glass-ionomer cements and their derivatives should therefore be applied in all situations where tissue repair is required. 5 They owe their ability to release ions to their silicate filler content, which continuously releases and recharges fluoride, and to their structural inner porosity, which allows water to flow through the material, leading to the dissolution of the filler.…”
mentioning
confidence: 99%
“…The addition of fluoride to restorative materials has attracted the attention of dental researchers and clinicians due to the possibility of their use as a reservoir releasing small amounts of fluoride, especially in patients with high caries risk (2). The story of the recognition and exploration of fluoride's ability to prevent caries occurrence or progression is long and interesting (3).…”
Section: Introductionmentioning
confidence: 99%